2017
DOI: 10.1021/acs.cgd.7b00463
|View full text |Cite
|
Sign up to set email alerts
|

Smart Polymorphism of Thiacalix[4]arene with Long-Chain Amide Containing Substituents

Abstract: A problem of controlled (smart) formation of polymorphs was solved for a set of tert-butylthiacalix­[4]­arene derivatives with four N-(2-acetoxyethyl)­carbamoylmethoxy substituents at the lower rim with 1,3-alternate, cone, and partial cone conformations. For this, an effective polymorph screening with a reproducible influence of preparation history was achieved using guest vapor inclusion and a standard state of host glass powder. By this procedure with consequent guest release and heating, the ability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…The glass of the same calixarene in another conformation allows detecting 1% vol. of benzene in hexane (Gataullina et al, 2017). A similar crystallization behavior was observed for glassy polymers (Gao et al, 2012), which have a less pronounced concentration threshold for the good component in binary solvent due to the incomplete crystallization.…”
Section: Crystallization Selectivity Of Amorphous Hostsupporting
confidence: 66%
See 3 more Smart Citations
“…The glass of the same calixarene in another conformation allows detecting 1% vol. of benzene in hexane (Gataullina et al, 2017). A similar crystallization behavior was observed for glassy polymers (Gao et al, 2012), which have a less pronounced concentration threshold for the good component in binary solvent due to the incomplete crystallization.…”
Section: Crystallization Selectivity Of Amorphous Hostsupporting
confidence: 66%
“…The activation of this process with guest vapors may be selective. Such selectivity was observed visually for a compact glass of calixarene (Gataullina et al, 2015(Gataullina et al, , 2017 and using an atomic force microscopy for thin amorphous films of dipeptides (Ziganshin et al, 2015). Amorphous dipeptides may have three options in contact with guest vapors depending on the guest molecular structure: (1) crystallization, (2) gel formation, (3) intact host morphology (Ziganshin et al, 2017).…”
Section: Crystallization Selectivity Of Amorphous Hostmentioning
confidence: 95%
See 2 more Smart Citations
“…Mention should also be made about polyplexes based on thiacalixarene derivatives, which are used for DNA packaging and have promising applications in biomolecular delivery systems and long-term storage of human genetic material [ 25 ]. Among other things, the controlled (smart) formation of polymorphs based on thiacalixarene derivative are also known [ 30 ]. Thus, according to previous contributions and applications of thiacalix[n]arenes it may be concluded that these macrocycles are promising candidates for constructing 2D nanostructures, especially different polymorphs that can be used in medicine for the development of modern pharmaceuticals, diagnostic agents and new generation materials.…”
Section: Introductionmentioning
confidence: 99%